2007
DOI: 10.1111/j.1365-2966.2007.11668.x
|View full text |Cite
|
Sign up to set email alerts
|

Supercritically accreting stellar mass black holes as ultraluminous X-ray sources

Abstract: We derive the luminosity–temperature relation for the supercritically accreting black holes (BHs) and compare it to the data on ultraluminous X‐ray sources (ULXs). At super‐Eddington accretion rates, an outflow forms within the spherization radius. We construct the accretion disc model accounting for the advection and the outflow, and compute characteristic disc temperatures. The bolometric luminosity exceeds the Eddington luminosity LEdd by a logarithmic factor (where is the accretion rate in Eddington unit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

45
869
4

Year Published

2008
2008
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 532 publications
(918 citation statements)
references
References 50 publications
45
869
4
Order By: Relevance
“…After reanalysis of 2007 and 2008 VLA observations, we agree with the conclusion of Cseh et al (2012) that the previously reported emission was likely not due to compact emission from a radio flare, though we cannot entirely rule out a radio flare with the current data. Microquasar flares (Blundell et al 2011;Corbel et al 2012;Punsly & Rodriguez 2013) are observed to be approximately 1 − 10 Jy at a distance of ∼ 8 pc, which corresponds to 4 − 40 µJy when scaled for the distance of 3.9 Mpc to IC 342, on the order of the unresolved emission of 63 µJy we find in the 2007 If the emission in the previous VLA observations was due to a radio knot, we can set a lower limit to its linear size based on the resolution of the 2011 JVLA observations. The beam diameter of the naturally weighted 4.9 GHz image is 0.5", and in order for the source observed in previous VLA observations to fall below 3σ per resolution element, it must be spread across more than two beams in the higher resolution observations, corresponding to a linear size of 13 pc at 3.9 Mpc.…”
Section: Discussionmentioning
confidence: 62%
“…After reanalysis of 2007 and 2008 VLA observations, we agree with the conclusion of Cseh et al (2012) that the previously reported emission was likely not due to compact emission from a radio flare, though we cannot entirely rule out a radio flare with the current data. Microquasar flares (Blundell et al 2011;Corbel et al 2012;Punsly & Rodriguez 2013) are observed to be approximately 1 − 10 Jy at a distance of ∼ 8 pc, which corresponds to 4 − 40 µJy when scaled for the distance of 3.9 Mpc to IC 342, on the order of the unresolved emission of 63 µJy we find in the 2007 If the emission in the previous VLA observations was due to a radio knot, we can set a lower limit to its linear size based on the resolution of the 2011 JVLA observations. The beam diameter of the naturally weighted 4.9 GHz image is 0.5", and in order for the source observed in previous VLA observations to fall below 3σ per resolution element, it must be spread across more than two beams in the higher resolution observations, corresponding to a linear size of 13 pc at 3.9 Mpc.…”
Section: Discussionmentioning
confidence: 62%
“…The illuminating radiation spectrum is flat in the range of 7 -12 keV, as it is expected in supercritical accretion disks (Poutanen et al 2007). Comptonization may extend and flatten the spectrum to higher energies.…”
mentioning
confidence: 68%
“…The soft excess is observed in the spectra of ULXs with the soft component temperature of T ∼ 0.1 keV (Stobbart, Roberts, & Wilms 2006), which is similar to that found in SS 433. If the ULXs or some of them are nearly face-on versions of SS 433, one may adjust their soft X-ray components to the outer funnel walls radiation (Poutanen et al 2007).…”
mentioning
confidence: 99%
“…They suggested that around the Eddington limit ULXs appear with broad disc-like X-ray spectra, whilst at higher accretion rates a two-component X-ray spectrum emerges. In the two-component spectra, a radiatively driven wind likely provides the soft component (Poutanen et al 2007;Kajava & Poutanen 2009), and the hard spectral component possibly originates from either a central cool, optically thick Comptonizing corona or the hot disc itself with a large colour correction (Middleton et al 2011a;Kajava et al 2012). Although it was originally suggested that the precise balance of the two components depended on the accretion rate, with softer wind-dominated spectra occurring in the most super-Eddington sources, it now seems likely that the inclination of the system also plays a key role in determining the observed spectrum (e.g.…”
Section: Introductionmentioning
confidence: 99%